IMPLEMENTASI METODE DEMONSTRASI BERBANTUAN MEDIA AUDIO VISUAL UNTUK MENINGKATKAN KETERAMPILAN MENDEKLAMASI PUISI DI SEKOLAH DASAR - Lilis Herliyanti (LINGUISTIK MIKRO, MAKRO DAN SASTRA, 2025)
Researcher This study aims to improve students' poetry declamation skills through demonstration methods assisted by audio-visual media in elementary schools. This study is a Classroom Action Research (CAR) involving 31 students with data collected through observation, interviews, and tests. Data analysis was carried out quantitatively to calculate the average value and learning completeness, and qualitatively to observe students' learning activities. The results showed that the implementation of this method was effective in improving students' poetry declamation skills. In cycle I, the average class value reached 71.45 with classical completeness of 51.61% (not complete). After improvements in cycle II, the average student value increased to 80.97 with classical completeness of 87.10% (complete). Observations of teacher and student activities also showed an increase, from an average of 75% (good category) in cycle I to 100% (very good category) in cycle II. In conclusion, the demonstration method assisted by audio-visual media successfully improved students' poetry declamation skills while achieving indicators